A national sample of developmentally disabled adolescents with obesity and their utilization of preventive dental care services - Tran, Nini C.; Wells, Christine R.; Atchison, Kathryn A.; Bhoopathi, Vinodh (Frontiers in Oral Health, 2023)
Background: Previous literature indicates that adolescents with developmental disabilities and obesity may have more oral health complications than healthy adolescents. However, dental care utilization among adolescents with developmental disabilities (DDs) and obesity is unclear. We investigated the differences in the utilization of preventive dental services between this high-risk group of adolescents and those with no DDs or obesity.Methods: Parent-reported data of adolescents 10 to 17 years (n=68,942) from the 2016 to 2019 National Survey of Children's Health was used. In addition to descriptive and bivariate statistics, we ran three multiple logistic regression models guided by Andersen's Behavioral Model of Health Services Use, predicting the use of dental cleanings, fluoride treatments, and dental sealants.Results: Among adolescents with DDs and obesity, dental cleanings, fluoride treatments, and dental sealant utilization prevalence were 76%, 48%, and 21%, respectively. In comparison, adolescents with no DDs or obesity had a prevalence of 83%, 50%, and 19%, respectively.Multiple logistic regression analysis showed that adolescents with DDs and obesity did not significantly differ in their receipt of dental cleanings (p=.07), fluoride treatments (p=.55), and dental sealants (p=.23) compared to those with neither DDs nor obesity. Adolescents with DDs but no obesity were 22% and 30% more likely to receive fluoride treatments (p<.0001) and dental sealants (p<.0001), respectively.Conclusions: Fewer than half of adolescents with DDs and obesity utilized fluoride treatments, and less than one quarter utilized dental sealants but used all three preventive services at the same rate as those with no DDs or obesity.